Successful Preclinical Development of Gene Therapy for Recombinase-Activating Gene-1-Deficient SCID - Laura Garcia-Perez (Molecular Therapy: Methods & Clinical Development, 2020)
Recombinase-activating gene-1 (RAG1)-deficient severe combined immunodeficiency (SCID) patients lack B and T lymphocytes due to the inability to rearrange immunoglobulin and T cell receptor genes. Gene therapy is an alternative for those RAG1-SCID patients who lack a suitable bone marrow donor. We designed lentiviral vectors with different internal promoters driving codon-optimized RAG1 to ensure optimal expression. We used Rag1−/− mice as a preclinical model for RAG1-SCID to assess the efficacy of the various vectors. We observed that B and T cell reconstitution directly correlated with RAG1 expression. Mice with low RAG1 expression showed poor immune reconstitution; however, higher expression resulted in phenotypic and functional lymphocyte reconstitution comparable to mice receiving wild-type stem cells. No signs of genotoxicity were found. Additionally, RAG1-SCID patient CD34+ cells transduced with our clinical RAG1 vector and transplanted into NSG mice led to improved human B and T cell development. Considering this efficacy outcome, together with favorable safety data, these results substantiate the need for a clinical trial for RAG1-SCID.